Antimicrobial susceptibility of bifidobacteria - Yazid, A.M.; Ali, A.M.; Shuhaimi, M.; Kalaivaani, V.; Rokiah, M.Y.; Reezal, A. (Oxford University Press, 2000)
A.M. YAZID, A.M. ALI, M. SHUHAIMI, V. KALAIVAANI, M.Y. ROKIAH AND A. REEZAL. 2000. Eighteen Bifidobacterium strains were tested for their susceptibility to a range of antimicrobial agents. All the strains tested, including the reference culture Lactobacillus acidophilus CH2, were susceptible to several groups of antimicrobial agents, they were cephalosporin (cefamandole, cefazolin, cefaperazone, cefoxitin), polypeptide (bacitracin), macrolide (erythromycin), penicillin (amoxicillin), phenicol (chloramphenicol) and β-lactam (imipenem). Fourteen strains were resistant to more than 10 antibiotics. The reference culture was resistant to only three antibiotics. The results showed that bifidobacteria are resistant to a wide range of antimicrobial agents.